The Factors contributing to the success of the 'OH So Heavenly' brand. Case study: OH So Heavenly - Glover, Lauren (The IIE, 2016)
The Oh So Heavenly brand is a beauty and pampering range that is sold solely within Clicks outlets in South Africa. The brands range was researched in order to determine the various factors contributing to the success of the brand. Consumers perceptions of the brand was the core focus of the research, allowing the findings to suggest further improvements for the brand. The research was done in order to understand how the brand has succeeded and to understand the brand awareness within the market. The research was conducted through qualitative research methods, including interviews with Oh So Heavenly Management and female consumers with four well-known shopping centres in the greater Durban area. Whilst the research was qualitative the findings have been tabulated in a quantitative manner to illustrate and bring clarity to the findings. Each research objective has been presented and the findings are assessed and discussed. Throughout the research paper, it was apparent that more than half of the interviewed respondents became aware of the brand through receiving it as a gift, respondents are attracted to the brand through its packaging and this therefore leading to Oh So Heavenly’s occasional gift packaging being extremely popular and powerful. Respondents considered the brands products to be well priced relative to competing brands, the products offer good quality throughout the brands range and they considered the brand to be good value for money. A common theme throughout this objective was the respondents view in the consumer perceiving the brand to be a premium product, yet the price is affordable for the majority. Various recommendations such as longer-term brand building, emphasis on label information and greater awareness to the entire brand range are highlighted within the research paper.
The Theses
Keywords: OH So Heavenly brand; Brand success; Consumers perceptions; Gift packaging; Affordable